HUSBANDS' PERCEPTIONS AND EXPERIENCES IN CARING FOR WIFE WITH CERVICAL CANCER: A QUALITATIVE PHENOMENOLOGICAL STUDY - Komariyah, Siti Nurul; Fitriana, Farida; Lestari, Pudji (Indonesian Midwifery and Health Sciences Journal, 2024)
Background: Cervical cancer ranks fourth for cancer that is often experienced by women worldwide and all ages with an estimated 604,127 new cases (6.5%), 342,000 deaths and about 90% of these cases occurred in low- and middle-income countries in 2020. In terms of psychoneuroimmunology, physical and emotional stress can have an impact on the immune system. Husband support with anxiety levels in cervical cancer patients undergoing chemotherapy, data was obtained that 7 out of 12 cervical cancer patients experience lower levels of anxiety when getting support from their husbands because patients feel more comfortable, calm and happy. This study aims to explore the perceptions and experiences of husbands while caring for their wives suffering from cervical cancer. Method: This research was conducted using qualitative methods with a phenomenological approach. The research subjects or informants in this study are husbands who treat wives with cervical cancer at Dr. Soetomo Surabaya Hospital who meet the inclusion and exclusion criteria From the results of semi-structured interviews, the researcher took the following steps, organizing and preparing the data to be analyzed, reading and viewing all the data, coding all the data, using the coding as material for creating descriptions, connecting between themes, and providing interpretation and meaning about the theme.Result: In this study, researchers found four dominant perceptions of husbands caring for their wives who had cervical cancer. These perceptions are most participants did not know about cervical cancer, all participants felt negative emotions when they learned about the complaints experienced by wives, various forms of support were given by participants to wives, all participants hoped for the recovery of wives. In the section on husbands' experiences in caring for wives with cervical cancer, researchers found five experiences experienced by husbands. These experiences include: all participants' wives experienced bleeding complaints, all participants experienced changes in terms of conjugal sexual relations, most participants had bad concerns about wife disease, the majority of participants never used poly palliative or pain-free services, most participants hoped that administrative services at Dr. Soetomo Surabaya Hospital would be faster. Conclusion: Cervical cancer affects and changes all aspects of women's lives and their families including for husbands of patients, therefore the care given to cervical cancer patients should be carried out holistically